PREREQUISITES FOR ENSURING THE CONFIDENCE LEVEL IN GNSS OBSERVATIONS (PANGEEA, 2025)
According to the regulations in force, each newly determined point should have at least 3 independent position vectors. In this context, simulations can be made on the one hand by highlighting and extracting locations at the maximum reception range of distances from a permanent GPS station (80km), and on the other hand, in the context of checking, creating, or developing some networks, the new points should be determined having at least 3 independent vectors linked to the RNSGP (National Network of GPS Permanent Stations - NNGPS) within 75% of the maximum reception distance (to increase the confidence level of the measurements). Practically, based on these regulations, it should be checked whether and to what extent the requirement is met at the level of the determined point as the centroid of the researched area.
Keywords: GNSS; RNSGP; measurement; satellite availability; spatial analysis; GIS; geoprocessing